The Nexus among Good E-Governance Practice, Decentralization, and Public Administration for Sustainable Local Development - Worya Balisany; Hale Özgit; Husam Rjoub (Discrete Dynamics in Nature and Society)
The formulation and implementation of development-oriented public policies, particularly in a post-conflict state like Iraq, requires empirical investigation. Consequently, this study investigates the effect of effective e-governance practices and decentralization on public administration in the Erbil district of Iraq. The purpose of this study is to determine the role of decentralization as a mediator between good e-governance practices and public administration in relation to the sustainable local development of the Erbil city. The sample of 409 employees of the Erbil municipality who participated in the survey was analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) with the assistance of WarPLS 7.0. The results of the study revealed a significant correlation between e-governance practices and decentralization and public administration. In addition, it was discovered that decentralization has a significant effect on public administration. The finding of a significant negative relationship between e-governance and decentralization suggests that e-governance has a negative impact on decentralization in Erbil. The implications of the study are discussed, and the study suggests that devolving power and authority to subunits in Iraq would enhance public administration and promote sustainable local development.